Adherence to guideline‐recommended process measures for squamous cell carcinoma of the head and neck in Ontario: Impact of surgeon and hospital volume. (1st February 2016) - Eskander, Antoine; Monteiro, Eric; Irish, Jonathan; Gullane, Patrick; Gilbert, Ralph; de Almeida, John; Brown, Dale; Freeman, Jeremy; Urbach, David R.; Goldstein, David P.
Abstract: Background: The purpose of this study was to measure adherence rates to guideline‐recommended process measures in patients with head and neck cancer. Methods: A total of 5720 patients who underwent surgery for head and neck cancer in Ontario between 1993 and 2010 were identified from administrative databases. Adherence to 4 guideline‐recommended processes of care was measured and stratified by hospital and physician case volume. Results: Seventy‐two percent of patients received preoperative head and neck imaging, 83% received preoperative chest imaging, 58% received preoperative multidisciplinary consultation, and 77% had appropriate follow‐up visits. Higher surgeon and hospital surgical volumes were associated with higher adherence rates. Conclusion: Adherence rates to guideline‐recommended processes of care in the surgical management of patients with head and neck cancer in Ontario were moderate and should be improved. Although adherence rates seem proportional to surgical volume, even the highest volume centers have room to improve. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E1987–E1992, 2016